Nitrofurantoin-Induced Pulmonary Toxicity: Mechanisms, Diagnosis, and Management - Alan D. Kaye; Shivam S. Shah; Leon LaHaye; John A. Hennagin; Anna K. Ardoin; Alexandra Dubuisson; Shahab Ahmadzadeh; Sahar Shekoohi (Toxics)
Nitrofurantoin, a commonly prescribed antibiotic for urinary tract infections, has been associated with rare but potentially serious pulmonary toxicity, which can present in acute, subacute, or chronic forms. Acute toxicity typically manifests in the form of hypersensitivity pneumonitis, which is characterized by fever, dyspnea, and eosinophilia, often resolving rapidly after drug discontinuation. However, chronic toxicity can lead to interstitial lung disease with progressive fibrosis, causing significant and sometimes irreversible pulmonary impairment. The pathophysiology of nitrofurantoin-induced lung injury is thought to involve oxidative stress, immune-mediated mechanisms, and direct cytotoxic effects; however, the exact pathways remain incompletely understood. Clinical diagnosis is challenging due to nonspecific symptoms that often resemble other respiratory conditions, leading to delays in recognition and treatment. Radiographic findings vary, with acute cases showing diffuse ground-glass opacities, while chronic cases may demonstrate reticular interstitial changes and fibrosis. The discontinuation of nitrofurantoin is the primary intervention, but corticosteroids may be beneficial, particularly in chronic cases with persistent inflammation or fibrosis, though their efficacy remains uncertain. Given the risk of long-term respiratory complications, heightened awareness among healthcare providers is essential for early diagnosis and intervention. Future research is needed to better define risk factors, improve diagnostic criteria, and explore alternative treatment strategies that mitigate the potential for pulmonary toxicity while maintaining effective antimicrobial therapy. This review explores the pathophysiology, clinical presentation, diagnostic challenges, and management strategies for nitrofurantoin-induced pulmonary toxicity.